Pengaruh Non-Performing Loan (NPL) dan Loan to Deposit Ratio (LDR) terhadap Return on Assets (ROA) pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2022–2024 - Shafwan Juldan; Vitayanti Fattah; Cici Rianty K. Bidin; Erwan Sastrawan Farid (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the effect of Non-Performing Loans (NPLs) and the Loan-to-Deposit Ratio (LDR) on Return on Assets (ROA) at banking companies listed on the Indonesia Stock Exchange for the period 2022–2024. This study employs a quantitative approach using secondary data in the form of banks’ annual financial reports. The sampling technique utilized purposive sampling, resulting in 15 banks selected as the study sample, comprising a total of 45 data observations. The analysis method employed is panel data regression using the Random Effects Model (REM) approach with EViews 13. The results indicate that NPL has a negative and significant effect on ROA. This indicates that as the level of non-performing loans increases, bank profitability tends to decline. Meanwhile, the LDR does not have a significant effect on ROA, suggesting that high levels of credit disbursement do not necessarily improve bank profitability. Simultaneously, both NPL and LDR have a significant effect on ROA.